2018
DOI: 10.1089/jamp.2016.1339
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Drug Delivery Following Continuous Vibrating Mesh Nebulization and Inspiratory Synchronized Vibrating Mesh Nebulization During Noninvasive Ventilation in Healthy Volunteers

Abstract: During NIPPV with a single-limb circuit bilevel ventilator, the use of inspiratory synchronized vibrating mesh nebulization may improve pulmonary drug delivery compared with conventional continuous vibrating mesh nebulization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Compared to the current commercially available continuous VMN, the inspiration synchronized VMN did not generate clinically relevant increment of inhaled dose, particularly at high gas flows. However, this finding was not surprising, as the inhaled dose was only slightly higher with inspiration synchronized VMN than continuous VMN in the previous in vitro and in vivo adult studies during noninvasive ventilation [11,12], while the inhaled dose was found to be even lower with inspiration synchronized VMN than continuous VMN during neonatal invasive ventilation in both in vitro and in vivo studies [23,24]. Additionally, all these studies found the delivery time with inspiration synchronized VMN was two-to threefold longer than continuous VMN [11,12,23,24].…”
Section: Clinical Implicationmentioning
confidence: 79%
See 3 more Smart Citations
“…Compared to the current commercially available continuous VMN, the inspiration synchronized VMN did not generate clinically relevant increment of inhaled dose, particularly at high gas flows. However, this finding was not surprising, as the inhaled dose was only slightly higher with inspiration synchronized VMN than continuous VMN in the previous in vitro and in vivo adult studies during noninvasive ventilation [11,12], while the inhaled dose was found to be even lower with inspiration synchronized VMN than continuous VMN during neonatal invasive ventilation in both in vitro and in vivo studies [23,24]. Additionally, all these studies found the delivery time with inspiration synchronized VMN was two-to threefold longer than continuous VMN [11,12,23,24].…”
Section: Clinical Implicationmentioning
confidence: 79%
“…However, this finding was not surprising, as the inhaled dose was only slightly higher with inspiration synchronized VMN than continuous VMN in the previous in vitro and in vivo adult studies during noninvasive ventilation [11,12], while the inhaled dose was found to be even lower with inspiration synchronized VMN than continuous VMN during neonatal invasive ventilation in both in vitro and in vivo studies [23,24]. Additionally, all these studies found the delivery time with inspiration synchronized VMN was two-to threefold longer than continuous VMN [11,12,23,24]. As such, the authors argued if it was worthwhile to use inspiration synchronized VMN [11,12,23,24].…”
Section: Clinical Implicationmentioning
confidence: 79%
See 2 more Smart Citations
“…Continuous generation of aerosol by nebulizers JN or VMN, in-line with HFNC, results in wastage to the atmosphere during the expiratory phase. Synchronized aerosol generation with patient’s spontaneous breathing increases inhaled dose during both invasive [ 53 ] and noninvasive ventilation [ 54 , 55 ]. With a prototype breath-synchronized VMN, Li and colleagues reported inhaled dose was higher with breath-synchronized versus continuous aerosol generation when placed close to the patient with HFNC gas flow ≥ 10 L/min.…”
Section: Factors Influencing Trans-nasal Aerosol Deliverymentioning
confidence: 99%